RFID Asset Monitoring Laboratory Environment - Jamaludin, Nur Alya Maisarah; Ahmad, Nur Azliza (Multidisciplinary Applied Research and Innovation, 2026)
This project deals with developing a smart lab equipment management system using RFID and IoT technologies. Presently, various educational institutions use manual logbooks or outdated systems to keep track of valuable tools like multimeters and oscilloscopes, which creates room for potential loss, misuse, or improper resource management. The system, therefore, aims to cater to those inconveniences by automating the borrowing and return of lab equipment through RFID tags and an ESP32 microcontroller. Each event is logged in real time into a cloud database, and Telegram notifications are sent out for overdue alerts and unauthorized activities. The system performed well in tests and was proven to be fully accurate and responsive when managing equipment data. It greatly reduces human error and helps maintain responsibility while giving a scalable solution to modern labs. In brief, RFID and IoT technologies found a real-time asset tracking and monitoring solution in this project.